Pengembangan Sistem Informasi Manajemen Donasi dan Relawan Bagi Komunitas Sosial - Gusti Rachman Nico; Satrio Agung Wicaksono; Fajar Pradana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Turun Tangan Malang is one of the social communities that exist in Malang. Focus fields raised today is the issue of social education and community. Based on the results of interviews, this community has a problem on its own activities. The first is the problem of the difficulty of seeking funds. Ineffectiveness of fundraising led to the infusion of funds be insufficient and not quite cover the cost of activities is large enough. The second problem is the community has never existed for accountability activities, causing the community cannot convince donors to donate. The last problem is the number of volunteers who are not active, consequently each activity has a lack of volunteers because of uneven information. Based on these problems, it can be given a solution to develop a management information system that has a function to be able to solve the problem. The method used in system development is Evolutionary Prototyping where the method is chosen because it can minimize the lack of analysis of the system needs to be developed and ensure the system built according to customer desires. The result of this research is resulted 32 functional requirement and 1 non-functional requirement obtained from 2 iteration. From the results of testing a black box, it brings the results of 100% valid from 32 tested features. Based on compatibility testing, the tested system is capable of running well on any browser except on Internet Explorer 8 and 9. Based on UAT testing containing 6 questionnaires, got acceptance on all points on each questionnaire.